Tag cloud algorithm with the inclusion of personality traits - Supli, Ahmad Affandi; Shiratuddin, Norshuhada; Ab. Aziz, Azizi (Foundation of Computer Science, USA, 2014)
It is imperative to consider human different perspective in order to visualize the information data towards users.Many studies proved that personality traits are one of the most significant factors that must be considered to give meaningful value when us ers see a view.This study tries to give ample evidence toward adjusting visual features on tag cloud visualization techniques. Since there is no study has tried to create an algorithm that can customize tag cloud visual properties based on personality traits. Therefore, the main objective of this study is to make tag cloud algorithm with the inclusion of personality traits by adjusting two prominent visual features (color and shape) as an integration of layout.In addition, the utilization of RBS (rule bas e system) approach as artificial intelligent method is also taken into account to make knowledge base that stores the relationship between the proper personality elements and particular layout.This paper also discusses findings from satisfaction evaluation of prototyping, which comprises three dimensions facet: overall layout, color, and shape .The findings showed that the majority mean value for each dimension is categorized in agree scale (6-point), which indicates that respondents are satisfied with the tag cloud layout display generated by proposed algorithm.The findings suggest interface designers to be careful in selecting the appropriate tag clouds layout to be displayed for users with varying personality differences.